Comparison of clustering of 16S and 5S RNA genes of bacteria by their triplet composition - Ovchinnikova Iuliia; Leonov Vyacheslav (ITM Web of Conferences)
The study of biological macromolecules such as RNA and the search for novel methods to analyze them is a crucial task due to their fundamental importance in all living organisms. Currently, analyzing the information stored in the genome is a complex process, and it is essential to find new ways to comprehend the functions and structures of genes and their interactions. This paper analyzes the clustering of bacteria based on the triplet composition of 5S and 16S RNA genes using elastic maps derived from frequency dictionaries of triplets. We have created indexed databases of 16S and 5S RNA genes and performed a comparative analysis of their clustering. We have determined the taxonomic composition of the identified clusters and analyzed the relationship between the structure of these clusters and the taxonomy of the bacteria.